Revisiting the clinico-radiological features of an unusual inguino-labial swelling in an adult female. (September 2022) - Vinoth, T.; Lalchandani, Ankit; Bharadwaj, Swastik; Pandya, Bharati
Abstract: Introduction: Processus vaginalis in females or the canal of Nuck was first described by the Dutch anatomist Anton Nuck in 1691 (Ranschaert and Worsley, n.d.; Brainwood et al., 2020 [1, 2]). Its patency after birth predisposes to congenital presentations like hydroceles, encysted hydroceles and hernias presenting as an unusual inguino-labial swelling. It gets obliterated by first year of life and hence anomalies related to its patency in adult hood are even rare. It is hence important to be familiar with the clinico-radiological aspects of such a presentation when it is encountered. Case report: Case presentation is of an adult woman of 36 years with hydrocele of the canal of Nuck. Discussion: We proceed to discuss the clinico-radiological features and variations of this entity in our case report. Conclusion: In conclusion, differential diagnosis of female inguino-labial swellings need detailed evaluation to exclude the possibility of rare entities. Highlights: Adult Hydrocele of Canal of Nuck is an uncommon entity. It poses diagnostic dilemma in many circumstances. An appropriate assessment is the key to diagnosis.